Augmented Reality: Daily Prayers for Preschooler Student - Pradibta, Hendra (International Journal of Interactive Mobile Technologies (iJIM), 2018)
Education is one of the aspects that many synthesized with technology. Yet, this is contrary to the fact that where most of the learning materials are still based on text. This research aims to develop an alternative learning media by implementing Augmented Reality Technology for Preschooler students. Augmented Reality (AR) is an application that can combine the virtual object as text, pictures and animation into the real world. Development of Augmented Reality application uses Web Aurasma Based Studio, with learning materials of daily prayer for preschool student. The development of the characters and the animations were using Adobe Illustrator and Adobe After Effects. The results of the study showed that technology Augmented Reality can be used as an alternative learning media especially in the learning process in Preschool Al Furqon. This is because the content Augmented Reality in the form of animation can gives more understanding and attention for preschool student to follow the learning process